Ansa versus spiro selectivity in substitution reactions of a mono ansa fluorodioxycyclotriphosphazene derivative with diols. (4th November 2015) - Mutlu, Ceylan; Beşli, Serap; Yuksel, Fatma
Graphical abstract: The nucleophilic substitution reactions of cis -ansa fluorodialkoxycyclotriphosphazene with disodium salts of diols occur preferentially at the PCl2 groups rather than at the P(OR)Cl moieties and so spiro derivatives are the major product in the reactions. Abstract: In this study, regio-selectivity in the nucleophilic substitution reactions of a mono ansa fluorodioxycyclotriphosphazene derivative with diols has been investigated. The cyclotriphosphazene derivative, N3 P3 Cl4 [OCH2 (CF2 )3 CH2 O] (1 ), was reacted with the disodium salts of 1, 3-propanediol and tetraethyleneglycol in THF solution at a 1:1 M ratio and eight new products (2 –6, 7a, 7b and8 ) were formed. These products were separated and characterized by elemental analysis, mass spectrometry, 1 H and 31 P NMR spectroscopy. The crystal structures of2, 3, 5, 6 and7a have been characterized by X-ray crystallography. The spiro derivatives (3, 6 ) were formed as the major product in the reactions of compound1 with both diols.